Original articleThe brain immune response in human prion diseases - Szpak, Grażyna M.; Lewandowska, Eliza; Lechowicz, Waldemar; Wierzba-Bobrowicz, Teresa; Kulczycki, Jerzy; Bertrand, Ewa; Pasennik, Elżbieta; Dymecki, Jerzy (Folia Neuropathologica, 2006)
A study of microglial activation and its contribution to the CNS immune response was performed on the brain autopsy material of 40 patients with definite sporadic Creutzfeldt-Jakob disease (sCJD). Spatial patterns of microglial activation and prion protein disease-associated (PrPd) deposition were compared in cerebellar and cerebral cortices using immunohistochemical (IHC) activation markers. Morphological phenotype forms of microglial cells in activation stages were assessed immunohistochemically (IHC). The immune inflammatory response dominated by microglia was found to be a characteristic feature in CJD. Differences in the intensity and patterns of microglial activation corresponded to variable patterns of PrP deposition, whereas the morphological phenotype forms of microglia were specific for activation stages. The presence of activated microglial cells in the various activation stages regardless of illness duration indicates continuous microglial activity and microglial contribution to the spread of infection for the whole symptomatic period of the disease. Remarkable vacuolar degeneration changes of numerous microglial cells in different activation stages including homing stage may suggest dysfunction of microglial immune surveillance in human sCJD that can significantly contribute to transmissible spongiform encephalopathy (TSE) pathogenesis.